The mycobiome of Pocillopora acuta in Singapore - Rabbani, Golam; Huang, Danwei; Wainwright, Benjamin J. (Coral reefs, 2021)
Despite their recognized importance in terrestrial and aquatic ecosystems, marine fungi, especially those associated with host organisms, remain poorly studied. Corals contain diverse communities of microbes that play important roles in adapting to disturbance and promoting host health, but studies on coral-associated fungal communities are conspicuous by their absence. Here, we comprehensively characterized the fungal communities and diversity associated with 97 unrelated coral colonies of Pocillopora acuta from nine islands in Singapore. We depleted coral DNA prior to PCR amplification of the fungal barcoding region (ITS1) to minimize issues of preferential host DNA amplification. This approach produced over a hundred times greater proportion of reads that were of fungal origin (75%) than previous studies, allowing us to more precisely characterize the associated fungal communities. We found no spatial structuring of fungal communities based upon sampling location, and provide evidence that suggests coral-associated fungi are more than just pathogens within their hosts. Many have been putatively identified as saprotrophs that are likely involved in making nutrients available for their host, and others may be possible symbiotrophs. Characterization of host-associated fungal communities provides valuable understanding—including information on the coral holobiont and how it functions—on a frequently overlooked, yet important microbial group.